(3eNJUQ aj GdJGQjNs
(3ChdgG (B:s
(3GdMeO ddg GdebOS HLejY GddZGJ hHYO aEfi deG hbaJ Ydi JGQjN GdEeGe GdWHQi QMeg Gddg , QCjJ ajg ef GdJWhjd ai GdTQhM s
(3BNQgG (B:s
(3hGbGe HOjhGf GdLjT NeSI hGQHYjf SfI heGJ ai UaQ SJ hKdGKjf hSJ eFI aEf GdcJGH jbhd (B: (3ef CaJNQ adjaJNQ HGdQH Je s
(3ai BNQ cd UaMI jejfkG hTeGdkGs
(3QJHg GdeDda Ydi SfhGJ GdgLQI hGNJUQg ef eUGOQ GdJGQjN GdeWhdI cJGQjN GdWHQi hZjQgs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 - (3U (B176 s
Keywords: (3GdJGQjNs